Digital Marketing And Price On Iswa Computer Sales Volume - Danis Unita Dewi; Varid Martah; Donny Arif (FAKULTAS EKONOMI UNIVERSITAS MAARIF HASYIM LATIF, 2022)
This study aims to determine the effect of digital marketing and price perceptions on computer sales volume. This study uses the dependent variables, including Digital Marketing, Price and the dependent variable, Sales Volume. Researchers approach with quantitative methods. The population in this study were Iswa Computer consumers in Surabaya. Using quantitative research methods with multiple linear regression analysis techniques, validity test, reliability test, classical assumption test, T-test and coefficient of determination test. The number of samples that meet the criteria for purposive sampling on Iswa Computer is 96 respondents. The research results partially by using the T-test that digital marketing variables positively and significantly affect sales volume. Testing the hypothesis using the T-test that the price variable positively and significantly affects sales volume.